Technology-Integrated Formative Assessment and the Predictive Role of Motivational Constructs on Conceptual and Procedural Knowledge in Chemistry - Hagos, Tadesse; Andargie, Dereje (Journal of Education Technology, 2024)
Many countries, including Ethiopia, efforts to employ formative assessment are complicated by a variety of challenges that lead to poor practices. Technology has the ability to play a crucial role in learning-supporting formative assessment methods. However, the bulk of previous formative assessment research did not rely on technology. Therefore, this study aims to analyze the differences in motivation between the two experimental and one comparison groups, as well as the impact of five motivational predictors in learning chemistry. To achieve the purpose, a quasi-experimental pretest-posttest design was adopted. The motivation questionnaire, the chemical equilibrium conceptual and the procedural tests were utilized to collect data. One-way ANOVA and multiple linear regression analysis were used to evaluate the data. In terms of improving students' motivation to understand chemical equilibrium, technology-integrated formative assessment processes outscored conventional approaches and formative assessment strategies on their own, according to the findings. According to a significant regression equation, the five motivating components of research have a significant impact on the conceptual and procedural knowledge test scores.  Individual predictors were investigated further, and it was shown that intrinsic motivation and grade motivation were both positive, significant predictors of conceptual test scores, whereas grade motivation was a positive, significant predictor of procedural knowledge test scores. Technology-integrated formative assessment procedures were shown to be more effective at increasing students' motivation to study chemical equilibrium than the other two groups.